2010
DOI: 10.1637/9103-101309-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Hemagglutinin Genes of 12 H9N2 Influenza Viruses Isolated from Chickens in Iran from 2003 to 2005

Abstract: In the present study, the hemagglutinin genes from 12 influenza viruses of the H9N2 subtype were isolated from chicken flocks in different provinces of Iran from 2003 to 2005, amplified and sequenced. All of the 12 isolates showed similar sequences at the cleavage site, RSSF/GLF, bearing eight potential glycosylation sites and sharing the characteristic deduced amino acid residues alanine-190, glutamine-226, and glutamine-227 at the receptor-binding site. Ten out of these 12 isolates possessed leucine at posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Efficient virus replication in dogs and mice was also described [44,45]. The virus is now endemic and many reports described virus isolation or seroprevalence in chickens, turkeys and wild birds [39,[46][47][48][49][50][51][52][53]. Vaccination was used in the field to mitigate the socioeconomic impact of the virus.…”
Section: Iranmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient virus replication in dogs and mice was also described [44,45]. The virus is now endemic and many reports described virus isolation or seroprevalence in chickens, turkeys and wild birds [39,[46][47][48][49][50][51][52][53]. Vaccination was used in the field to mitigate the socioeconomic impact of the virus.…”
Section: Iranmentioning
confidence: 99%
“…S2). Many mutations in AIV H9N2 in ME and NA associated with adaptation to mammals have been described [25,26,46,48,50,59,75,84,95,105,118,119].…”
Section: Genetic Relatedness Of H9n2 In the Me And Namentioning
confidence: 99%
“…Meanwhile, A/chicken/Central Sulawesi/M9206/2016 and A/layer/Indonesia/ CentralJava-01/2017 have 180-T. According to Moosakhani et al (2010), the level of binding affinity is associated with the presence of amino acid residue at position 180, in which 180-A (Alanine) is the lowest, 180-T is medium, and the strongest is 180-V (Valine).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the studies conducted by Karimi, Torogi, and MoosaKhaniet alconfirmthesequences -Moosakhani et al, 2010. Withrespect tothe changes of12amino acids in H9N2virusesisolated frompoultryinIranin 2010by thestudy ofMoosaKhani, in case of thecirculationofthe virus in the Iran poultry farms, the incidence ofpointmutationsofthese virusesispossible (Moosakhani et al, 2010).…”
Section: Introductionmentioning
confidence: 85%
“…In the study conducted by MoosaKhaniet al(2010) on 12 isolated H9N2virusesfrom Iran,it was found that10of12viruses hadleucine amino acid at position of 226 and the two other viruses hadglutamineamino acid (Moosakhani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%